Complete mitogenome of Antheraea formosana Sonan, 1937 (Lepidoptera: Saturniidae): an endemic silkmoth in Taiwan. Issue 3 (4th March 2022) - Cheng, An-Ping; Huang, Chi-Chun; Cheng, Yu-Tzu; Tseng, Yu-Wei; Wang, Chih-Chiang; Lai, I-Ling; Hung, Kuo-Hsiang
Abstract: The complete mitogenome of an endemic silkmoth in Taiwan, Antheraea formosana, was determined using Illumina next-generation sequencing. The mitogenome is 15, 318 bp in length and consists of 13 protein-coding genes (PCGs), two rRNAs, 22 tRNAs, and one non-coding control region. The overall base composition of the mitogenome showed a high A + T bias, and the A + T content (80.2%) was significantly higher than the G + C content (19.8%). All PCGs use the typical ATN as the initiation codon, with the exception of cox2, which begins with GTG, respectively. The complete mitogenome was used to reconstruct a phylogenetic tree, indicating that A. formosana is more closely related to Antheraea assamensis than other Antheraea species, with 93.19% nucleotide similarity.